2023
DOI: 10.22541/au.167725626.68946264/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral clearance in end-to-end continuous process for mAb purification: Total flow-through integrated polishing on two columns connected to virus filtration

Abstract: There are few reports of the adoption of continuous processes in bioproduction, particularly the implementation of end-to-end continuous processes, due to difficulties such as feed adjustment, production batch demarcation, and incorporating virus filtration. Here, we propose an end-to-end continuous process for a monoclonal antibody (mAb) with three integrated process segments: upstream production processes with pool-less direct connection, pooled low pH virus inactivation with automated pH control and a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The detailed analysis of the two‐connected FTC column operation with VF attached to the 2nd column including viral clearance studies has been reported in Shirataki et al (2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed analysis of the two‐connected FTC column operation with VF attached to the 2nd column including viral clearance studies has been reported in Shirataki et al (2023).…”
Section: Resultsmentioning
confidence: 99%
“…The recovery of Run 7 was lower due to the misoperations (some of the pool was lost). The detailed analysis on Run 4 was published in Shirataki et al (2023).…”
Section: Resultsmentioning
confidence: 99%
“…A fully end‐to‐end continuous biomanufacturing process must include continuous virus filtration (David et al, 2019). Research on continuous virus filtration processes is still in early stages (Bohonak et al, 2021; Fan et al, 2021; Lute et al, 2020; Shirataki et al, 2023). It is crucial to elucidate the differences between batch and continuous operations, and to master the methods for designing operation parameters of continuous processes based on batch operations.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing robust and efficient models require proper model calibration and suitable calibration experiments (Chen et al, 2022; Chen, Chen, et al, 2023; Chen, Yao, et al, 2023; Yang et al, 2024). In virus filtration, pressure operations have been primarily applied and modeled, rather than considering constant flux processes (Shirataki et al, 2023, 2021). Recently, Malakian et al (2022) developed a PF‐CST‐CST model to describe the RTD of virus filtration in constant flux processes.…”
Section: Introductionmentioning
confidence: 99%